2016
DOI: 10.1007/s10910-016-0608-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hylleraas–CI atomic integrals by integration over the coordinates of one electron. IV. An improved algorithm for three-electron kinetic energy integrals

Abstract: An improved algorithm to evaluate the nonrelativistic three-electron Hylleraas-Configuration Interaction (Hy-CI) kinetic energy integrals over Slater orbitals and the Hamiltonian in Hylleraas coordinates is shown. The resulting analytical expressions are general for all quantum numbers of the orbitals. From there, the restriction of employing orbitals with quantum numbers l ≤ 2 of the above algorithm presented in paper I of this series has been removed. With the new algorithm it is possible, in the direct inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Moreover the calculations of the ground state of helium atom have proven to be computationally faster when using the Kolos and Roothaan algorithm. Nevertheless it is important to test the direct method of evaluation, because this is the one which has to be used for the three-electron kinetic energy integrals when using the Hamiltonian in Hylleraas coordinates, since in the three-electron case the Kolos and Roothaan transformation cannot be used [35].…”
Section: B Hylleraas-ci Two-electron Kinetic Energy Integralsmentioning
confidence: 99%
“…Moreover the calculations of the ground state of helium atom have proven to be computationally faster when using the Kolos and Roothaan algorithm. Nevertheless it is important to test the direct method of evaluation, because this is the one which has to be used for the three-electron kinetic energy integrals when using the Hamiltonian in Hylleraas coordinates, since in the three-electron case the Kolos and Roothaan transformation cannot be used [35].…”
Section: B Hylleraas-ci Two-electron Kinetic Energy Integralsmentioning
confidence: 99%
“…Some three-electron and four-electron integrals have been evaluated by Ruiz [44,45] by integration over the coordinates of one electron and calculated to a high degree of accuracy. Same method of evaluation was employed by Ruiz [46,47] to calculate the two-electron kinetic energy and the three-electron kinetic energy. Frolov et al [48] have investigated bound state spectra and properties of the doublet states in Li atom and some Li-like ions employing Hy-CI and CI methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that, if we make either a change (2 ⇆ 3) in equation( 44) or a change (3 ⇆ 1) in equation( 33), we get equation (47). Hence, by inspection, the following closed-form expression for I g 33 is obtained either from equation( 45) by performing a change (2 ⇆ 3) or from equation( 35) by making a change (3 ⇆ 1) :…”
mentioning
confidence: 99%